Improving the taxation system of forest resources on the basis principles of payment for forest use - N. N. Kalashnikova (Путеводитель предпринимателя)
The significance of issues related to improving the efficiency of the current system oftaxation of forest resources, taking into account the basic principles of payment for forest use, providing improvement of fiscal and control and regulatory significance of payments, are largely the basis for the functioning of the entire timber industry, are subject to submission of a scientific study. Taking into account the designated problems for the purposes of perfection of normative regulation of relations forest users in collecting payments for the withdrawal of forest rent, and full implementation of tax control in the implementation of the principle of payment for forest resources and sustainable forest management the task of revising their regulation with civil legal foundations of the building of the tax relations.